Problems of optimizing the energy consumption of households in the tasks of improving the energy efficiency of the housing sector - G. G. Grebenuk (Statistika i Èkonomika, 2018)
The aim of the work is to study the problem of optimizing energy consumption and practical application of methods for  improving energy efficiency in the housing sector. Optimization of  energy efficiency management allows to reduce the expenditure of  energy resources in the performance of various works, heating of buildings, etc. The creation of optimization methods will make it  possible to reduce payments for utilities in a short time, and in  general for the industry, will help reduce the consumption of various  resources and improve the ecological state of the region. Unlike  other approaches, the emphasis in this paper is on the convenience  and simplicity necessary for using this technique by the population in households. The proposed integrated approach uses methods of  probability theory, linear programming, heat exchange models. The  conducted research confirms the effectiveness of the solution  obtained and can serve as a basis for the creation of training and  research stands. The article consists of two parts: the first part  analyzes the leading works in this field and identifies the reasons  that make it difficult to apply the solutions proposed in these papers. Further, the statement of the problem was proposed and justified,  and a number of basic requirements to the mathematical model of  energy consumption, necessary for the constructed technique to be  used to optimize energy consumption in households, were  formulated. In the second part, a mathematical model of their  functioning is proposed using examples of specific household  electrical appliances. When researching existing methods for  optimizing energy consumption in households, problems were  identified that were difficult to apply these methods in practice and  recommendations were obtained that allowed to formulate the basic  principles of constructing an optimization technique that was  convenient for practical application. It was shown that when  constructing such a technique, the primary question is the data that  the user can provide. The minimum composition of input data was  determined, according to which the necessary algorithms for  optimizing energy consumption were designed. A number of  algorithms for determining some input indicators that are easy to use in households have also been proposed. Thus, the general plan of research in this paper is as follows:• carry out grouping of devices by the way of setting functionalrequirements;• determine the acceptable composition and type of input data forthe user;• define the minimum set of input data for formalizing the limitationof the total power consumption;• design optimization algorithms that work with the input dataspecified above. The most important results of the work performed are the following:• the methodology for forecasting the graph of the maximum totalpower consumption has been developed.• methods for optimizing energy consumption for each of the selected subsets of household appliances have been developed.• the optimization algorithms obtained have been simulated, which showed their operability, efficiency and the possibility of their practical application without any adaptation.Thus, the article proposes the solution of the problem of optimization of energy consumption in the housing sector, oriented to practical application.